«Війна б’є по наших душах…» Повномасштабне вторгнення в рефлексіях очевидців (Матеріали до української етнології, 2024)
Трагічний досвід українства з виживання в умовах сучасної війни фіксується у свідченнях очевидців, у мартирологах, що продовжуються кожного дня. Представлений корпус документів – важливе історичне джерело, форма збереження колективної пам’яті народу, доказова база про злочини ворогів для майбутніх судів над ними. В Інституті мистецтвознавства, фольклористики та етнології ім. М. Т. Рильського (ІМФЕ) цього року було опубліковано книгу «Культура повсякдення часів російсько-української війни» (Етнографічний образ сучасної України. Корпус експедиційних фольклорно-етнографічних матеріалів. Т. 12. Культура повсякдення часів російсько-української війни / [голов. ред. Г. Скрипник] ; НАН України ; ІМФЕ ім. М. Т. Рильського. Київ, 2024. 848 с.), яка містить близько 400 інтерв’ю зі свідками подій повномасштабної війни в Україні. Частину матеріалів, що не ввійшли до видання, публікуємо в цьому числі щорічника. Це зафіксовані у 2022–2023 роках автоетнографічні розповіді та щоденникові записи науковців Українського фольклорно-етнографічного центру ІМФЕ, представників київської інтелігенції. The tragic experience of Ukrainians in surviving in the conditions of modern war is recorded in the testimonies of eyewitnesses, in the martyrologies that continue every day. The submitted corpus of documents is an important historical source, a form of preservation of the collective memory of the people, and evidence-based information about the crimes of enemies for future trials against them. This year M. Rylskyi Institute of Art Studies, Folkloristics and Ethnology (IASFE) has published the book “Everyday Culture during the Russian-Ukrainian War” (SKRYPNYK, Hanna, ed.-in-chief. Ethnographic Image of Modern Ukraine. Corpus of Expeditionary Folklore and Ethnographic Materials. Vol. 12. Everyday Culture during the Russian-Ukrainian War. National Academy of Sciences of Ukraine; M. T. Rylskyi IASFE. Kyiv, 2024, 848 pp.). It contains about 400 interviews with the witnesses of the events of the full-scale war in Ukraine. We are publishing a part of the materials that haven’t been included in the edition in this issue of the annual. These are autoethnographic stories and diary entries of the scientists of the Ukrainian Folklore and Ethnographic Centre of the IASFE, the representatives of Kyiv intelligentsia, recorded in 2022–2023.